The Ideal of Renaissance period in English literature (Eurasian Journal of Learning and Academic Teaching, 2022)
This article analyzes the main features of Renaissance period and the well known character of Christopher Marlowe who idealize the period. In the article, there is a whole description of periodic aim and its usage to describe the hero of the drama, Tamburlaine the Great.